Genome-wide mapping and analysis of active promoters in mouse embryonic stem cells and adult organs - Barrera, Leah O.; Li, Zirong; Smith, Andrew D.; Arden, Karen C.; Cavenee, Webster K.; Zhang, Michael Q.; Green, Roland D.; Ren, Bing (Genome Research, 2008)
By integrating genome-wide maps of RNA polymerase II (Polr2a) binding with gene expression data and H3ac and H3K4me3 profiles, we characterized promoters with enriched activity in mouse embryonic stem cells (mES) as well as adult brain, heart, kidney, and liver. We identified ∼24,000 promoters across these samples, including 16,976 annotated mRNA 5′ ends and 5153 additional sites validating cap-analysis of gene expression (CAGE) 5′ end data. We showed that promoters with CpG islands are typically non-tissue specific, with the majority associated with Polr2a and the active chromatin modifications in nearly all the tissues examined. By contrast, the promoters without CpG islands are generally associated with Polr2a and the active chromatin marks in a tissue-dependent way. We defined 4396 tissue-specific promoters by adapting a quantitative index of tissue-specificity based on Polr2a occupancy. While there is a general correspondence between Polr2a occupancy and active chromatin modifications at the tissue-specific promoters, a subset of them appear to be persistently marked by active chromatin modifications in the absence of detectable Polr2a binding, highlighting the complexity of the functional relationship between chromatin modification and gene expression. Our results provide a resource for exploring promoter Polr2a binding and epigenetic states across pluripotent and differentiated cell types in mammals.
10.1101/gr.6654808